Implementation of strengthening character education at madrasah diniyah al-hidayah Karangnongko Klaten, central Java - Yasin Syafii Azami; Abid Nurhuda; Muhamad Kusmanudin; Salsabila Syifa; Nur Muhammad Lathif (STAI Darul Kamal Darul Kamal NW Kembang Kerang, 2024)
The education developed in Indonesia aims to make learning citizens (students) have four main characters, namely religious humans, individual humans, social humans, and citizens. Currently, a very serious social problem occurring around us is the destruction of the order of moral values or noble character (moral decadence). Madrasah Diniyah Al-Hidayah is one of the three main components of education (tri-educational centers), namely the community, which operates in the religious sector and is organized by the community for the community (self-help community) which is concerned with the importance of character education. So this research aims to describe the implementation of Strengthening Character Education at Madrasah Diniyah Al-Hidayah Kanoman Karangnongko Klaten. The data collection techniques used by researchers are observation, interviews, and documentation. The results of the research show that the implementation of strengthening character education at Madrasah Diniyah Al-Hidayah includes learning planning which refers to the philosophical basis to the empirical basis. Then the implementation of the process is manifested through a class-based approach, a culture-based approach at Madrasah Diniyah, and a community-based approach. Lastly is habituation which includes aspects of worship, behavior (character), and example.